Konsep Dakwah Dalam Novel Bidadari Bermata Bening (Analisis Wacana Teun Van Dijck Novel Bidadari Bermata Bening Karya Habiburrahman El Shirazy) - Evi Muyasaroh; Agus Setyawan; Khafidhoh Khafidhoh (Social Science Academic, 2023)
The novel is one of the print media that is effectively used to convey da'wah messages. The message conveyed from a novel is the intellectual experience and background of the social life of the writer. By reading a novel one can find out the message to be conveyed, the concepts that are instilled and the direction in which the author's thoughts are. This study aims to determine the concept of preaching about faith and the concept of preaching about love in the novel entitled Bidadari Bermata Bening by Habiburrahman El Shirazy. The method used in this research is library research by collecting data and information related to the research object in the form of the da'wah concept contained in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy. The concept in question is in the form of the concept of da'wah about faith and morals. The results of this study concluded that the concept of preaching about faith in the novel Bidadari with clear eyes, whose research focus is in the form of the concept of preaching about faith and the concept of preaching about love in the novel entitled Bidadari with Clear Eyes by Habiburrahman El Shirazy, has Islamic values ​​that are dominant towards the flow of Alhu Sunnah Wal Jama'ah.